Legal Protection Of Business Activities In Monopoly Practices And Unfair Competition Through Eletronic Transactions - Yurniawati Djakaria (Universitas Negeri Gorontalo, 2019)
Abstract: This study aims to determine how the legal protection of business actors in monopolistic practices and unfair competition through electronic transactions. The type of research used in this research is normative research which includes legal principles, legal systematics, legal history, and comparative law. The approach used in this research is the Legislative Approach The data analysis technique used in this research is the deductive method. The results of this study indicate that unhealthy business protection has an impact on business actors where the absence of regulations governing the setting of low prices is currently lacking. In addition, marketplace business actors have mushroomed by selling the same goods as those in the marketplace. So that sales through the marketplace have dominated offline retail business actors. The form of legal protection for activities carried out by the marketplace has been regulated by legislation on information and electronic transactions and unfair business competition practices but does not regulate in detail the existence of legal protection itself. Therefore, the role of government officials, both as policymakers and as supervisors and regulatory apparatus for a legal product, must make laws and regulations that can later become social engineering for all Indonesian people.Keywords: Protection; Competition; Monopoly.